Mixed-mode silica monolith as an efficient separation medium for capillary electrochromatography - Jemale, Alia Sofie (2010)
Silica monolith column having mixed-mode i.e., hydrophobic (C18) and anion exchange interaction was successfully synthesized by on-column modification of the hybrid tetramethoxysilanes (TMOS) and methyltrimethoxysilanes (MTMS) using octadecyldimethyl-(N-N-diethylamino)silane (ODS) and ion exchange monomer of N-[3-(dimethylamino)propyl]acrylamide (DMAPAA-Q) methyl chloride-quaternary salt, for the surface modification. The preparation of the ODS/DMAPAA-Q silica monolith column was carried out in a fused silica capillary column of 75 µm internal diameter. At each modification stage, the ODS/DMAPAA-Q silica monolith column was chromatographically characterized with micro liquid chromatography (µLC) and produced separation efficiencies of up to 43000 plates/min at the optimum velocity using the test mixture of alkylbenzenes, and 41800 plates/min for selected nucleotides. The ODS/DMAPAA-Q silica monolith column was also characterized physically with scanning electron microscope (SEM), and showed to have an average through-pore size and skeleton size of 2.2 µm and 2.0 µm, respectively. The ODS/DMAPAA-Q silica monolith column was then characterized in capillary electrochromatography (CEC) for the separation of inorganic and organic ions using a 50 mM phosphate pH 6.9 background electrolyte. The inorganic anions and organic ions were separated within 10 mins with column efficiency up to 114900 plates/min. The results suggest that modifying a silica monolith capillary column through in-situ polymerization of a monomer carrying a functional group can yield high efficiency columns for the ion-exchange-mode separation as well as for reversed-phased separations. The analysis of the porous silica monolith columns with CEC yields higher performance than CZE analysis for the separation of anions.